Divergent trends of ecosystem status and services in the Hexi Corridor - Zhu, Hanshou; Zhai, Jun; Hou, Peng; Gao, Haifeng; He, Yingli; Jin, Diandian; Xu, Ningning (Frontiers in Environmental Science, 2022)
In terms of ecosystem structure, quality, and service, we have constructed a total of 18 characteristic evaluation indicators that could reflect the “state change interaction” of the ecosystem and analyzed the Spatio-temporal change of the ecosystem in Hexi Corridor from 2000 to 2020. The results show that: 1. The improvement of ecosystem and service is more obvious in the areas with a better ecological background in the East. The supply and regulation services of the ecosystem are synergetic. 2. In the past 2 decades, the ecological conditions of the Hexi corridor have improved as a whole, and the hot spots for improving ecosystem quality and services have gradually moved eastward. 3. Ecosystem changes have significantly changed the quantity and relationship of ecosystem services, showing strong spatial heterogeneity. For example, the loss of natural vegetation in the central and eastern regions with good ecological backgrounds has improved the water conservation service and also enhanced the synergy between it and the supply service. From the perspective of the relationship between ecosystem regulation services and supply services, the coordination characteristics are weakened, but the performance of regions with a poor ecological background in the west is just the opposite. In short, the typical climate characteristics of dry land with little rain and the spatial pattern of water resource shortage not only jointly determine the ecosystem background of the region, but also bring significant spatial differences and greater uncertainties to the relationship between ecosystem transformation and ecosystem services. Therefore, dryland ecosystem management and protection should be based on detailed and differentiated ecosystem assessment, taking into account regional natural resource endowment, giving priority to improving the stability of the regional ecosystem and gradually increasing regional ecosystem services.